Prevalence of Neck pain and its effects on Quality of life of Software Engineers in Lahore - Amber Nasir, Mamoona Shaukat, Sajjad Ali Sajjad, Arif Ali Rana, Munazza Waseem, Hafiza Aroosa Syed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Neck pain is a sensation of discomfort in the dorsal and lateral side of cervical spine due to postural or mechanical faults. It affects health - status, work productivity and multiple interventions are used to treat neck pain. Aim: To check the prevalence of neck pain, its effects on quality of life of software engineers of Lahore city. Methodology: This was an observational study Cross-sectional survey. Three hundred and thirty eight participants with minimum one year of job experience in software house were included in the study. Neck pain disability and quality of life were observed by using NDI and SF-12 respectively. Data was entered and analyzed by SSS 22.0.s Results: Results showed the prevalence as mild, moderate, severe and complete neck pain disability in software engineers was 150(44.38%), 68(20.12%), 19(5.62%) and 3(0.89%) respectively and 98(28.99%) participants were without neck pain. There are more male participants 86(25.44%) without neck pain than female participants 12(3.55%) without neck pain. Neck pain showed no significant association with age of software engineers because p > 0.05 in chi-square test. There were fewer participants with excellent and poor physical health 8.28% and 10.36% respectively. Conclusion: Neck pain is common in software engineers of Lahore city. Neck pain is more prevalent in female software engineers as compared to male. Severe neck pain declined their Physical health and complete neck pain caused disability. They are facing the physical health issues with resulting limitations in their routine office work, physical activities and social activities. Neck pain is associated with gender and physical health of software engineers.